CYP4F22 gene mutations in patients with autosomal recessive congenital ichthyosis: Identification of two novel mutations - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2020)
Background: Autosomal recessive congenital ichthyosis (ARCI) is a genetically heterogeneous keratinization disorder, which is clinically classified into five main forms: Lamellar ichthyosis, congenital ichthyosiform erythroderma, harlequin ichthyosis, self-healing collodion baby, and bathing suit ichthyosis. Mutations in TGM1, ABCA12, ALOX12B, ALOXE3, NIPAL4, CYP4F22, PNPLA1, LIPN, and CERS3 genes have been described in patients with ARCI. However, in 20% of the ARCI patients, the genetic defect remains unknown. Materials and Methods: In this study, we investigated the mutations in the CYP4F22 gene in ARCI patients who do not have mutations in two common ARCI genes, NIPAL4 and TGM1. Twenty-two patients diagnosed with ARCI and having no mutations in TGM1 and NIPAL4 genes were included in the study. Their CYP4F22 genes were sequenced using the Sanger sequencing method. Results: In 5 of 22 (22.7%) ARCI patients, four different mutations, of which two were previously reported, were found. The two novel mutations were c.976C> T and c.1189C> T. The c.727C> T and c.1303C>T mutations were previously reported. Conclusions: This study expands the CYP4F22 mutation spectrum and to provide more accurate genetic counseling for patients at risk.
Keywords: Autosomal recessive; genetic diseases; mechanisms; ichthyosis; sanger sequencing; LAMELLAR ICHTHYOSIS; ATOPIC-DERMATITIS; SPECTRUM; FORM